Konfusianisme sebagai Sabuk Pengaman RRT - Muas, R. Tuty Nur Mutia Enoch (UI Scholars Hub, 2020)
The slogans propagated by Chinese leader Hu Jintao—namely “rise in peace”, “a harmonious socialist society”, and “a harmonious world”—reflects the country’s age-old Confucian values. Considering the fact that the PRC only recognizes communism as the state ideology and that Confucianism was subjected to harsh criticism during the Cultural Revolution era (1966–1976), the presence of Confucian values in PRC’s political propaganda becomes an interesting research topic. Both Confucianism and communism put the state as the center of power and sovereignty. This research used the historicalchronological approach by examining the attitude of the PRC government towards Confucianism from 1980 to 2012. Results show that such a consistent philosophy has been successful in strengthening the government’s legitimacy. As it continues to rise, the PRC needs to adopt a robust philosophical basis such as Confucianism to serve as part of its soft power. Confucianism has been adjusted to the country’s current situations and utilized so extensively for decades that it can be considered as PRC’s main vehicle for national development. This article examines and presents the historical role of Confucianism in PRC’s rise.